Transformasi Akad Jual Beli Syariah pada Bisnis Modern: Tinjauan Hukum dan Sengketa yang Muncul - Neni Hardiati Tresna (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The application of sale and purchase acad in modern business is an important aspect of sharia economic law. Shariah principle compliant sales acad not only ensures fairness and transparency in transactions, but also enhances trust between the parties involved. This article examines the transformation of Shariah sales acad in the modern business context, the challenges of its application, the underlying legal aspects, as well as the types of disputes that arise. A qualitative approach was used to analyze how the Shariah selling accord is adapted in modern business practices, including electronic and e-commerce systems. This article aims to provide comprehensive insights for business actors, academics, and regulators to optimize fair and sustainable Shariah-based selling practices. This study examines the adaptation and development of the concept of sales accord (al-Baiâ€™) within the framework of Sharia Economic Law (HES) along with modern business dynamics, particularly through digital platforms (e-commerce) and non-verbal transaction mechanisms (such as baiâ€™ al-muâ€™Äá¹ah in modern stores). The key issue is how the principles of Shariah, especially the pillars and valid requirements of the akad, are retained or transformed in contemporary practice, as well as the legal implications they pose. The results of the study indicate that a shift occurred from verbal sighat (ijab and qabul) to non-verbal and digital forms, which the majority consider valid by contemporary scholars based on the principle of â€˜urf (habit) so long as it fulfills the element of voluntarism (an tarÄá¸in), clarity of object (maâ€™qÅ«rangs babarang (maysur, tererba), and terrabah). This transformation could potentially give rise to disputes, especially regarding the validity of the digital ijab qabul, risk liability (á¸amÄn), and dispute resolution mechanisms in Shariah non-judicial institutions. The conclusion affirms the need for harmonization between jurisdictional flexibility of transactions and legal certainty in modern business regulation.